Estimating HIV incidence and number of undiagnosed individuals living with HIV in the European Union/European Economic Area, 2015 - Pharris, Anastasia (2017)
Helena Cortes Martins, Departamento de Doenças Infeciosas do Instituto Nacional de Saúde Doutor Ricardo Jorge, IP